A case of severe acute hepatitis of unknown etiology requiring liver transplantation in a child with adenovirus infection - V. A. Greshnyakova; M. K. Bekhtereva; L. G. Goryacheva; V. E. Karev; A. M. Komarova; A. I. Konev; Yu. V. Lobzin; A. N. Uskov; N. V. Skripchenko; K. V. Serednyakov (Журнал инфектологии)
The article presents a clinical observation of severe acute hepatitis of unknown aetiology with liver transplantation in a 16-year-old child, which occurred in October 2021. Initial symptoms were abdominal pain, diarrhea. The general wellbeing of the girl did not suffer, there was no fever, no intoxication syndrome. Over the next days, she began to notice the appearance of edema on the legs, an increase in the size of the abdomen. From the 10-11th day of illness – darkening of urine, acholia of feces, jaundice were observed. She was examined by a pediatrician, a biochemical blood test was performed, according to the results the girl was hospitalized with a diagnosis of acute hepatitis. According to the severity of the condition, she was hospitalized in the ICU. On admission she complained of abdominal pain, jaundice, edema, and weakness. On examination: jaundice, scleral icterus, hemorrhagic rash at the site of the tourniquet, bleeding from injection sites, hepatomegaly, anasarca. In blood tests: progressive anemia, thrombocytopenia, increased AST (with a decrease in dynamics against the background of progression of liver failure), a decrease in total protein and albumin, fibrinogen, prothrombin according to Quick. Laboratory excluded viral hepatitis A-E. The only infectious agent diagnosed was group F adenovirus in feces. By the third day of hospitalization developed of multiple organ failure, DIC. On the 4th day of hospitalization, the child was transferred to a specialized hospital, where an emergency liver transplantation was performed. The operation was successful, the child was discharged in a stable condition.